Ultra-short echo time cardiovascular magnetic resonance of atherosclerotic carotid plaque - Chan, Cheuk F (BioMed Central, 2010)
BACKGROUND: Multi-contrast weighted cardiovascular magnetic resonance (CMR) allows detailed plaque characterisation and assessment of plaque vulnerability. The aim of this preliminary study was to show the potential of Ultra-short Echo Time (UTE) subtraction MR in detecting calcification. METHODS: 14 ex-vivo human carotid arteries were scanned using CMR and CT, prior to histological slide preparation. Two images were acquired using a double-echo 3D UTE pulse, one with a long TE and the second with an ultra-short TE, with the same TR. An UTE subtraction (ΔUTE) image containing only ultra-short T2 (and T2*) signals was obtained by post-processing subtraction of the 2 UTE images. The ΔUTE image was compared to the conventional 3D T1-weighted sequence and CT scan of the carotid arteries. RESULTS: In atheromatous carotid arteries, there was a 71% agreement between the high signal intensity areas on ΔUTE images and CT scan. The same areas were represented as low signal intensity on T1W and areas of void on histology, indicating focal calcification. However, in 15% of all the scans there were some incongruent regions of high intensity on ΔUTE that did not correspond with a high intensity signal on CT, and histology confirmed the absence of calcification. CONCLUSIONS: We have demonstrated that the UTE sequence has potential to identify calcified plaque. Further work is needed to fully understand the UTE findings.